Analysis on community involvement in cultural activities: Transmission of ethnic language - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah (2013)
The paper review an analysis of community involvement in cultural activities especially in the form of ethnic language. Survey questionnaire was distributed in Melaka to measure and determine the level of community involvement in cultural activities.The research found significant similarities among the four cultured community within the study area and transmission of ethnic language are influenced by the demographic and socio-economic factor of the community